ANALISIS LITERASI SAINS SISWA SEKOLAH DASAR MENGGUNAKAN RASCH ANALYSIS MODEL (RAM) - Herianingtyas, Nur Luthfi Rizqa; Edwita, Edwita; Yarmi, Gusti (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
In the 21st century, a generation is needed that has the ability to be critical of scientific phenomena around them so that they are able to analyze, make decisions, and solve problems related to issues in their daily lives. Therefore, it is important for every citizen to have good scientific literacy, while the PISA results for Indonesian students' scientific literacy are still below the international average score. This research presents the results of a more comprehensive analysis of students' scientific literacy to identify students' strengths and weaknesses in each relationship between content, context and scientific literacy competency indicators. This type of research is descriptive quantitative research with data collection techniques through tests and data processing using the Rasch Analysis Model (RAM) assisted by Winstep software. From the Winstep output, it is known that the reliability of the instrument expressed in Cronbach's alpha is 0.64. This research was conducted on a sample of 50 elementary school students in Pacitan Regency. Based on the research results, it is known that question items that are difficult for students to work on are items that contain epistemic knowledge content with a local-national context and competence in interpreting data and evidence scientifically. Meanwhile, easy scientific literacy items contain factual knowledge content with personal context and competence in explaining phenomena scientifically. In the test results for eight scientific literacy indicators, it was found that male students' scientific literacy was higher than female students' scientific literacy indicators.